2020
DOI: 10.1016/j.addbeh.2020.106348
|View full text |Cite
|
Sign up to set email alerts
|

Examining the relationship between impulsivity-related personality traits and e-cigarette use in adults

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…In that study, we found e-cigarette use was positively associated with sensation seeking and lack of premeditation; positive and negative urgency predicted cigarette but not e-cigarette use (Doran & Tully, 2018). Another recent crosssectional study among European adults suggested urgency measures may be more closely related to use of cigarettes than e-cigarettes (Kale et al, 2020). Overall, the pattern of results suggests that, at least among emerging adults who are not yet daily users, e-cigarette use may be driven by the pursuit of positive reinforcement without concern for consequences, and not in response to acute affective states.…”
Section: Discussionmentioning
confidence: 72%
“…In that study, we found e-cigarette use was positively associated with sensation seeking and lack of premeditation; positive and negative urgency predicted cigarette but not e-cigarette use (Doran & Tully, 2018). Another recent crosssectional study among European adults suggested urgency measures may be more closely related to use of cigarettes than e-cigarettes (Kale et al, 2020). Overall, the pattern of results suggests that, at least among emerging adults who are not yet daily users, e-cigarette use may be driven by the pursuit of positive reinforcement without concern for consequences, and not in response to acute affective states.…”
Section: Discussionmentioning
confidence: 72%
“…Similar patterns have been found for the relationship with vaping, albeit with mixed results. In two prospective studies, externalising and internalising problems, reflecting poorer self‐control and depressive symptoms respectively, predicted e‐cigarette initiation in the national representative Population Assessment of Tobacco and Health Study of American youth aged 13 years [36], and greater impulsivity predicted the frequency of e‐cigarette use among 137 American young adult e‐cigarette users over time [37]; however, a correlational study of 720 UK adults ages 18 to 68 found few differences in impulsivity‐related traits between non‐users, e‐cigarette users, smokers and dual‐users [38]. Given the overall patterns, we hypothesize that lower levels of self‐control in adults could also predict an increased likelihood of transitioning to vaping over time among non‐users.…”
Section: Introductionmentioning
confidence: 99%
“…Addictive behaviors have been traditionally studied in relation to variable impulsivity. Coates et al [ 1 ], Kale et al [ 2 ] and Meikle et al [ 3 ] are examples of this. Regarding addictions, having a high degree of impulsivity can be explained by two accounts that are not mutually exclusive, according to Verdejo-García et al [ 4 ].…”
Section: Introductionmentioning
confidence: 99%